(3GdJgPjH aj JaSjQ GdbQBf GdcQjes - (3GdMGce CHj SYO GdMSf Hf cQGeI GdLTej GdHjgbj GdHQhbj,J (B494 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi gOGfG ddESdGe hOYGfG Edi OGQ GdSdGe s
(3BNQgG (B:s
(3BNQg eHJhQ , jfJgi HJaSjQ bhdg JYGdi (B:" (3EfeG jCeQce HGdShA hGdaMTGA hCf JbhdhG Ydi Gddg eG dGJYdehf (B" (3CKfGA JaSjQ ShQI GdHbQI s
(3cJHJ HQSe NRGfI GdabjI MejO Hf CMeO GdeMdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B289s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs